Research on Subway Construction Monitoring and Warning System Based on Internet of Things Technology. Issue 2 (April 2021) - Zheng, Xuezhao; Guo, Hang
Abstract: Aiming at the problems that the low specification, underinvestment and the low professional level of risk management existed in the subway construction at present, analyzed the construction demand of monitoring and warning system for subway construction, a king of subway construction monitoring and warning system based on internet of things technology was proposed. Internet of things, wireless communication, cloud computing and other technologies was exploited to comprehensive sense and monitor of the construction site; Researched the personnel positioning system based on Mesh technology to realize wireless self-organizing network of transmit data and improve positioning accuracy and response speed; By combining the video monitoring with wireless sensing technology, real-time monitoring of field operations was realized, ensure the safety of workers' lives and "zero hidden danger" in the field working environment; Data push technology was used to achieve mobile video monitoring, stagewise and classified management, improve the flexibility of safety management.